Nilai Karakter Peduli Lingkungan pada Anak Usia Dini melalui Pembelajaran Berbasis Projek - Yuliantina, Irma; Nurbani, Babay (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
Character for a child must be accustomed from an early age, children who are accustomed to good character values will care about the surrounding environment, and their social life will develop well too, they will be accustomed to maintaining personal hygiene and environmental cleanliness. This study aims to measure the relationship between project-based learning and the value of environmentally caring character in early childhood. This study used a descriptive method.  Qualitative is research that produces descriptive data in the form of written or spoken words from people observed. This research aims, Attitudes and Actions to always try to prevent damage to nature. Safeguarding nature from damage. Overcoming pollution from environmental destruction and caring for the surrounding environment.  The research stage consists of three stages, including the preparation stage, the field research stage and the data analysis stage, based on the results of research from 20 children showing:   , children who show an attitude to prevent damage to nature and use their rough muscles when cleaning the environment 100%, Protecting nature from damage, Overcoming pollution from environmental destruction, Actively express ingredients 95%, Choose materials and make decisions 90%, Care about the surrounding environment, Find cause and effect and tell experience 85%. This achievement concludes that the Character Value of Environmental Care in early childhood can be done through project-based learning.